CYP1A2 Genetic Variants and Breast Cancer Susceptibility in Women: Varian Genetik CYP1A2 dan Kerentanan Terhadap Kanker Payudara pada Wanita - Ghasaq Abd Alkareem Nouri; Hassan Risan Al-Rikabi (Universitas Muhammadiyah Sidoarjo, 2025)
Breast cancer remains a leading cause of cancer-related morbidity among women worldwide, with genetic susceptibility playing a crucial role in disease development. Cytochrome P450 1A2 is involved in estrogen metabolism and has been implicated in carcinogenesis through genetic polymorphisms affecting enzymatic activity. This study aims to investigate the association between the CYP1A2 rs17861162 polymorphism, family history, disease stage, and breast cancer risk in women from Thi-Qar Province, Iraq. A case-control design was applied, including 40 breast cancer patients and 20 healthy controls. Genomic DNA was extracted from blood samples, and polymerase chain reaction was used for genotyping. Statistical analyses were conducted using Chi-square tests, odds ratios, and confidence intervals. The results showed no statistically significant association between CYP1A2 rs17861162 genotypes or alleles and breast cancer risk, although the G allele demonstrated a non-significant 1.5-fold increased risk. Family history and disease stage were also not significantly associated with breast cancer occurrence. The novelty of this study lies in providing population-specific genetic evidence from an underrepresented region, contributing to the growing body of literature on CYP1A2 polymorphisms and breast cancer. These findings suggest that CYP1A2 rs17861162 alone may not serve as a reliable genetic biomarker, highlighting the need for larger, multiethnic studies to clarify its role in breast cancer susceptibility. Keywords: Breast Cancer, CYP1A2 Polymorphism, Genetic Susceptibility, Estrogen Metabolism, Cancer Risk Highlights: CYP1A2 rs17861162 shows no significant association with breast cancer risk G allele demonstrates a non-significant increased susceptibility trend Population-specific genetic evidence expands breast cancer genomics literature